138k views
6 votes
What is the true solution to the logarithmic equation below?
log₂ (6x)-log₂ (√x)=2

User Joe Okatch
by
5.6k points

1 Answer

4 votes

answer: x =
\\ (4)/(9\\)


log_(2) (6x) -
log_(2) (
√(x)) = 2

expand the expression:


  • log_(2)(6x) =
    log_(2) (6) +
    log_(2) (x)

  • log_(2) (
    √(x)) =
    log_(2) (
    x^{(1)/(2) })

transform the expression:


  • log_(2) (
    x^{(1)/(2) }) =
    (1)/(2) *
    log_(2) (x)

calculate the difference:


  • log_(2) (x) -
    (1)/(2) *
    log_(2) (x) =
    (1)/(2) *
    log_(2) (x)

multiply both sides by 2:


  • log_(2) (6) +
    (1)/(2) *
    log_(2) (x) = 2 is now 2
    log_(2) (6) +
    log_(2) (x) = 4

transform the expression:

  • 2
    log_(2) (6) =
    log_(2) (
    6^(2))

simplify the expression:


  • log_(2) (
    6^(2)) +
    log_(2) (x) =
    log_(2) (
    6^(2) x)

evaluate the power:


  • log_(2) (
    6^(2) x) =
    log_(2) (36x)

convert the logarithm into exponential form:


  • log_(2)(36x) = 4 is now
    36x = 2^(4)

evaluate the power:


  • 2^(4) = 16

divide both sides by 36:


  • (36)/(36) x =
    (16)/(36) which is x =
    (4)/(9)
User Samturner
by
6.0k points